2023
DOI: 10.1002/vzj2.20251
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring spatiotemporal soil moisture variability in the unsaturated zone of a mixed forest using electrical resistivity tomography

Abstract: European forests are suffering considerably from the consequences of the droughts of recent years, and the exact reasons and influencing factors for this are still not fully understood. This study was conducted to characterize the changes and dynamics of soil moisture in a mixed forest in northern Bavaria within 1 year. Since electrical resistivity correlates well with soil water content, we used two‐dimensional electrical resistivity tomography (ERT) monitoring and time‐lapse analyses to supplement punctual m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 85 publications
2
2
1
Order By: Relevance
“…In Chen et al (2019) andPeddinti et al (2020), an RMSE between ERT and soil water probe ranged from 0.02 to 0.027 (depth dependent) and 0.03 cm 3 cm À3 , respectively. Moreover, the Archie law parameters obtained through calibration and field conditions (as presented in Table 1) are consistent with those found in previous research conducted by Nijland et al (2010) and Rieder and Kneisel (2023). This alignment with prior studies adds confidence to the validity of our ERT-based θ determination and reinforces the reliability of the results obtained in this study.…”
Section: Water Content Determination By Ertsupporting
confidence: 90%
See 2 more Smart Citations
“…In Chen et al (2019) andPeddinti et al (2020), an RMSE between ERT and soil water probe ranged from 0.02 to 0.027 (depth dependent) and 0.03 cm 3 cm À3 , respectively. Moreover, the Archie law parameters obtained through calibration and field conditions (as presented in Table 1) are consistent with those found in previous research conducted by Nijland et al (2010) and Rieder and Kneisel (2023). This alignment with prior studies adds confidence to the validity of our ERT-based θ determination and reinforces the reliability of the results obtained in this study.…”
Section: Water Content Determination By Ertsupporting
confidence: 90%
“…The calibration results demonstrated high performance with an RMSE of 0.017 cm 3 cm À3 (Figure 8), and the validation RMSE was only slightly higher at 0.021 cm 3 cm À3 . These results surpass the literature's standards, as previous studies by Rieder and Kneisel (2023) reported depth-dependent RMSE values ranging from 0.01 to 0.02 cm 3 cm À3 . In Chen et al (2019) andPeddinti et al (2020), an RMSE between ERT and soil water probe ranged from 0.02 to 0.027 (depth dependent) and 0.03 cm 3 cm À3 , respectively.…”
Section: Water Content Determination By Ertcontrasting
confidence: 65%
See 1 more Smart Citation
“…While during snowmelt the decrease in resistivity related to groundwater upwelling extended toward the end of the transect, and hence the stream, in late summer, this feature ends when entering the forested area at x = 220 m. We interpret this as a reduction in soil moisture due to water uptake by the trees at this location (Figure 8f). Significant reduction in soil moisture within forested areas have also been observed in other studies with soil and bedrock conditions comparable to the eastern part of the transect (Peskett et al, 2020;Rieder & Kneisel, 2023).…”
Section: Subsurface Dynamics During Summer Monsoonsupporting
confidence: 82%
“…Their results show that forest strips have a significant impact on the hillslope hydrology by lowering the groundwater table and reducing soil moisture, compared to adjacent grassland. Electrical resistivity tomography (ERT) monitoring also allows to assess soil moisture dynamics below single trees in detail (Fäth et al, 2022), and Rieder and Kneisel (2023) show that individual tree species show different subsurface water demands and dynamics.…”
mentioning
confidence: 99%